BUKTI EKSISTENSI TUHAN (Integrasi Ilmu Kalam dengan Filsafat Islam Ibnu Sina) - Anik Masriyah (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2020)
AbstractIslamic philosophy and the science of kalam have the similar discussion about God. However, if Islamic philosophy, namely Ibn Sina’s thoughts really put the ratio first whereas the science of kalam also enclose the naqli argument. The discussion about whether God can be seen or not in the science of kalam has dissent, especially Mu’tazilah and Asy’ariyah. Indeed, currently humans can’t see God, but we can prove the existence of God through his creation, which is in the from of this universe. Ibnu Sina through his theory of emanation said that the universe was created from the emanation of the One and then gave birth to thr first reason to the tenth reason. In this modern times, it is easier to see evidence of God’s existence as technology develops.